Concurrent Etoposide, Steroid, High-dose Ara-C and Platinum chemotherapy with radiation therapy in localised extranodal natural killer (NK)/T-cell lymphoma, nasal type. Issue 16 (November 2015) - Michot, Jean-Marie; Mazeron, Renaud; Danu, Alina; Lazarovici, Julien; Ghez, David; Antosikova, Anna; Willekens, Christophe; Chamseddine, Ali N.; Minard, Veronique; Dartigues, Peggy; Bosq, Jacques; Carde, Patrice; et al.
Abstract Purpose Radiation combined with chemotherapy has recently been proposed to treat patients with localised extranodal natural killer (NK)/T lymphoma (ENKTL), nasal type. However, the modalities of the chemoradiotherapy combination and drug choices remain a matter of debate. We conducted a concurrent chemoradiotherapy (CCRT) study with the ESHAP (Etoposide, Steroid, High-dose Ara-C and Platinum) regimen. Methods An induction phase with two upfront courses of CCRT delivering a 40 Gy dose of radiation concurrently with two cycles of the ESHAP chemotherapy regimen, followed by a consolidation phase with 2–3 cycles of ESHAP chemotherapy alone. Results Thirteen patients with localised ENKTL nasal type were enrolled between January 2005 and December 2014. The median age was 62 years. Ten and three patients had Ann Arbor stage IE and IIE disease, respectively. They all completed the induction CCRT phase. A median of two consolidation ESHAP cycles were delivered. During consolidation, 8/13 (62%) patients had a reduction in the number of chemotherapy cycles or reduced chemotherapy doses, due to haematologically adverse events. The other five patients (38%) received the full number of ESHAP cycles of chemotherapy scheduled without a dose reduction. All but one patient (92%) experienced grade 3–4 haematological toxicity. The main non-haematological grade 3–4 toxicity was mucositis in 6/13 (46%) patients. All but one patient (92%) achieved a complete remission. Two-year overall survival was 72%. Conclusions With optimal management of the specific toxicities induced by this treatment modality, CCRT with the ESHAP regimen yielded high efficacy against localised ENKTL, nasal type.